Croatian and Serbian private forest owners' perceptions of energy wood mobilization: survey results and relevance for future bioeconomy. Issue 4 (4th July 2017) - Halder, Pradipta; Paladinić, Elvis; Stevanov, Mirjana
ABSTRACT: In recent years, new policies have emerged in Europe related to both bioenergy and bioeconomy. The study investigated perceptions of the Croatian and Serbian non-industrial private forest owners (NIPFs) concerning energy wood mobilization from forests owned by them. A total of 232 NIPFs from the two countries participated in the study. The NIPFs perceived that they did not have adequate knowledge of selling energy wood, its price, and energy wood entrepreneurship. According to the NIPFs, the most significant obstacle to mobilizing energy wood from private forests was the lack of proper forest roads in their countries. Among the economic instruments, the NIPFs favored subsidies and guaranteed market over tax reduction for mobilizing energy wood and establishing energy wood entrepreneurship. Their main motivation for energy wood production appeared to be expected income from such an activity. It also appeared that the NIPFs would prefer supplying energy biomass from new plantations and harvesting residues instead of using their existing forests. The study provided a number of recommendations for the policy makers in Croatia and Serbia on improving the preconditions for energy wood mobilization from private forests and linking it with the bioeconomy by addressing the issues related to policy, infrastructure, and market development.